(untitled) (Shanti Journal, 2024)
Everyone in the world deserves equal economic, political and social rights and opportunities. Every individual’s rights and opportunities should be recognized and protected within the society where they belong. This is the state of “social justice”. Social justice is inevitable as it promotes fairness and equity across different aspects of society. However, underprivileged people are denied social justice in an unjust society, resulting in missed opportunities across various sectors of life. As a result, a person may experience a cascade of difficulties in other different areas too. Burhan’s hero Maila Tharu, and other characters also go through similar phases of unfavorable conditions, struggles and sufferings. This proves to be the destiny of underprivileged people in an unjust society, where the quest for social justice is elusive. This paper explores and analyzes persistent struggles for social justice in Mahananda Dhakal’s Burhan. It attempts to explore different ways of exploitation and victimization of such innocent and helpless characters. This paper also contends that such characters are denied rights and opportunities within the society, and kicked out from their own land and properties. Through the critical analysis of the character’s experiences, the paper examines the elusive nature of social justice in Burhan. The paper finally argues that Burhan serves as a powerful commentary on the ongoing struggle equity and the critical need for transformative change.